WOWEN SEXUAL DESIRES EXPERIENCES DURING HONEYMOON PERIODS - Nunuk Yuliastri; Nining Febryana; Dwi Izzati Budiono (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground: Honeymoon is a vacation trip that is usually done by newly married couples to celebrate their wedding. The  most beautiful moment awaited by newlywed couples, where everything still looks beautiful and sweet like honey. This study aimed to explore married women’s experience of their sexual desire during their honeymoon periods. Methods: The researcher conducted this qualitative study on six eligible married women who met the requirements for reproductive age. Data were collected using semi structured–interviews and analyzed using thematic methods. All of the participants in this study were obtained through purposive sampling. After being conducted, each interview was transcribed verbatim and read several times to achieve the sense of the whole and then, the key terms were highlighted as codes. After the initial classification of the codes, categories and themes gradually appeared. Results: a theme was found and divided into two categories:1) passionate and emotional sexual desires;2) Spontaneous and sensitive sexual desires Conclusions: During their honeymoon period, the majority of women experienced sexual desire that is spontaneous, sensitive or easily rises when stimulated, hence its getting more excited, and often this sexual desire even being so selfish and emotional, especially at their 'first night'.Keywords: experiences, honeymoon, qualitative research, sexual desire, women